Information and communication privacy in wireless sensor networks - Salami, Abdulazeez F.; Hussaini , Muktar; Bello-Salau, Habeeb; Anwar, Farhat (IIUM Press, 2011)
This chapter places special emphasis on sensor networks applications in a battlefield.When a sensor network is used to monitor soldiers' movements in a battlefield, information about the soIdiers' whereabouts is sent back to the base station and accessed by commanders in the headquarters as shown in Figure 33.1. Before the fight, planes fly over the battlefield and deploy the sensors. These sensors organize themselves into a network and transmit data collected from the battlefield and send them back to the base station